Pengaruh New Normal terhadap Kegiatan Pariwisata di Indonesia - Suharto Suharto; MADE PRASTA YOSTITIA PRADIPTA (STABN Raden Wijaya Wonogiri, 2021)
Tourism industry has become one of the main sectors which drives the gross domestic product and increases the national income in Indonesia. However, with the appearance of COVID-19, Indonesia’s economy collapsed and coincided with the other industries. The impact of the virus affects tourism wholly either in operational and economy negatively. The impact of the virus affects tourism wholly either in operational and economy negatively. This condition finally changes the era from normal to new normal which also changes the perspective and behaviour of all parties. The effects and solutions from the new normal existence become an interesting object for scholars and tourism experts. This paper aims to identify the effects and solution of the new normal’s existence in Indonesia’s tourism industry. The qualitative method is used in this research using the literature studies from the secondary data sets. The results show that the new normal turns out to bring a positive side in the tourism industry because of the innovations and solutions which appear from a new way of thinking and regulation. Therefore, the influences of the new normal, especially in Indonesia will be explained in more detail in this research.